Constraining AGN feedback model with SZ profile - Tanimura Hideki; Hinshaw Gary; McCarthy Ian G.; Van Waerbeke Ludovic; Aghanim Nabila; Ma Yin-Zhe; Mead Alexander; Tröster Tilman; Hojjati Alireza; Moraes Bruno (EPJ Web of Conferences, 2022)
Relativistic jets from AGN have a wide range of impacts on galaxy groups and clusters and are key for understanding their formation and physical properties. However, this non-gravitational process is not well understood. Galaxy groups with shallow gravitational potentials are ideal laboratories to study and constrain the AGN feedback model. We studied hot gas in ∼66,000 SDSS LRG halos with an average halo mass of 3×1013 M⊙ using the Planck tSZ map. We have detected their average tSZ radial profile at ∼17σ and compared it with the cosmo-OWLS cosmological hydrodynamical simulations with different AGN feedback models. The best agreement has been obtained for the AGN 8.0 model in the simulations. We have also compared our measured tSZ profile with the prediction from the universal pressure profile assuming the self-similar relation and found them consistent if the model accounts for the clustering of neighboring haloes via a two-halo term.